XPS and AFM investigations on silver-based photoimageable thick film systems - Umarji, Govind; Ketkar, Supriya; Hawaldar, Ranjit R.; Gosavi, Suresh W.; Patil, Kashinath; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Microelectronics International, 2008)
Purpose - The purpose of this paper is to ascertain chemical changes occurring at various stages involved in processing of silver-based photoimageable thick films; and to determine ensuing topographical features which other wise appeared to be hindered in 2D scanning electron microscopy. Design/methodology/approach - Surface sensitive techniques, viz. X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM) were used. Findings - Interfacial adhesion of silver film with substrate (Al(2)O(3)) was specifically looked into with respect to role played by photoimaging (before and after exposure to ultra-violet light). XPS results revealed occurrence of subtle chemical changes in terms of unsaturation to saturation in C-C bonding and also an interesting C-Al bonding which presumably improves mechanical adhesion of unfired film with the alumina substrate. AFM was carried out to examine the surface roughness, particle size, and microstructure of film which are very important from the standpoint of high-frequency applications. Originality/value - Surface sensitive techniques like XPS and AFM were exclusively used in order to characterize silver-based photoimageable thick films.
Keywords: microscopy; Silver; thick film circuits; X-rays

Field emission properties of Al-doped ZnO nanostructures - Navale, Shalaka C.; Sheini, Farid Jamali; Patil, Sandip S.; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A.; Gosavi, Suresh W. (Journal of Nano Research, 2009)
Field emission from Al-doped ZnO nanostrcutures has been investigated in planar diode configuration under ultra high vacuum conditions. The Al-doped ZnO nanostructures were synthesized by co-precipitation method with varying aluminium concentrations. The as- synthesized product was characterized by x-ray diffraction, scanning electron microscope and energy dispersive x-ray analysis. The threshold field required to draw a current density of similar to 1 mu A/cm(2) was observed to be similar to 2.0 V/mu m and similar to 2.3 V/mu m for Al-doped ZnO nanostructures synthesized with aluminium concentrations of 1% and 3%, respectively. The Fowler- Nordheim (F-N) plots for both the specimens exhibit non-linear behaviour, which is observed to be specimen dependent. The nonlinearity observed in the F-N plots has been interpreted on the basis of the theory of electron emission from semiconductor emitters. The field enhancement factors, estimated from the slope of the F-N plots, are found to be similar to 9.3 x 10(3) and 3.9 x 10(3) for 1% and 3% Al-doped ZnO emitters, respectively. The high values of the field enhancement factor Suggest that the emission is from the nanostructures. The emission current stability measured at the preset value of similar to 2 mu A over a period of more than three hours is found to be fairly stable. The results indicate use of Al-doped ZnO nanostructures as promising emitters for field emission based devices.
Keywords: field emission; Fowler-Nordheim plots; Nanostructures; ZnO

Hierarchical CdS nanostructure by Lawesson's reagent and its enhanced photocatalytic hydrogen production - Pandit, Vikram U.; Arbuj, Sudhir S.; Hawaldar, Ranjit R.; Kshirsagar, Pradnya V.; Deshmukh, Amarsinh J.; Ambekar, Jalindar D.; Mulik, Uttam P.; Gosavi, Suresh W.; Kale, Bharat B. (RSC Advances, 2015)
Lawesson's reagent (LR) has been effectively exploited for the synthesis of hierarchical architectures of cadmium sulphide (CdS) nanostructures for the first time. The X-ray diffractograms of the as synthesised CdS nanostructures confirm the formation of hexagonal CdS. The broadness of the XRD peaks clearly indicates the nanocrystalline nature of CdS with average crystallite size of 4 nm. A FESEM study revealed the formation of hierarchical nanostructures, whereas a TEM study showed that the hierarchical arrangement is composed of nanosized CdS particles. A band-gap i.e. 2.4 eV was derived from diffuse reflectance spectroscopy. The photoluminescence spectrum showed an emission peak at 535 and 568 nm which can be attributed to band-edge emission and surface emissions or possible metal vacancies, respectively. Considering the band-gap within the visible region, the photocatalytic hydrogen evolution performance of these CdS nanostructures was performed under visible light irradiation from hydrogen sulphide and water, respectively. Utmost hydrogen evolution i.e. 14 136 mu mol h(-1) g(-1) and 2065 mu mol h(-1) g(-1) was observed over a naked CdS nanostructure via H2S and water decomposition, respectively. The amount of hydrogen obtained by H2S splitting is much higher as compared to earlier reports.

Nanostructured 2D MoS2 honeycomb and hierarchical 3D CdMoS4 marigold nanoflowers for hydrogen production under solar light - Kadam, Sunil R.; Late, Dattatray J.; Panmand, Rajendra P.; Kulkarni, Milind V.; Nikam, Latesh K.; Gosavi, Suresh W.; Park, Chan J.; Kale, Bharat B. (Journal of Materials Chemistry A, 2015)
Unique two dimensional (2D) honeycomb layered MoS2 nanostructures and hierarchical 3D marigold nanoflowers of CdMoS4 were designed using a template free and facile solvothermal method. The MoS2 structure is depicted with a sheet like morphology with lateral dimensions of 5-10 mu m and a thickness of similar to 200 nm and a honeycomb nanostructure architecture produced via the self-assembling of vertically grown thin hexagonal nanosheets with a thickness of 2-3 nm. The 3D CdMoS4 marigold nanoflower architecture comprised thin nanopetals with lateral dimensions of 1-2 mu m and a thickness of a few nm. The CdMoS4 and MoS2 structures displayed hydrogen ( H-2) production rates of 25 445 and 12 555 mu mol h(-1) g(-1), respectively. The apparent quantum yields of hydrogen production were observed to be 35.34% and 17.18% for CdMoS4 and MoS2, respectively. The 3D nanostructured marigold flowers of CdMoS4 and honeycomb like 2D nanostructure of MoS2 were responsible for higher photocatalytic activity due to inhibition of the charge carrier recombination. The prima facie observation of H-2 production showed that the ternary semiconductor confers enhanced photocatalytic activity for H-2 generation due to its unique structure. Such structures can be designed and implemented in other transition metal dichalcogenide based ternary materials for enhanced photocatalytic and other applications.

Seeded on-surface supramolecular growth for large area conductive donor-acceptor assembly - Goudappagouda; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam; Gosavi, Suresh W.; Babu, Sukumaran Santhosh (Chemical Communications, 2015)
Charge transport features of organic semiconductor assemblies are of paramount importance. However, large-area extended supramolecular structures of donor-acceptor combinations with controlled self-assembly pathways are hardly accessible. In this context, as a representative example, seeded on-surface supramolecular growth of tetrathiafulvalene and tetracyano-p-quinodimethane (TTF-TCNQ) using active termini of solution-formed sheaves has been introduced to form an extended assembly. We demonstrate for the first time, the creation of a large-area donor-acceptor assembly on the surface, which is practically very tedious, using a seeded, evaporation-assisted growth process. The excellent molecular ordering in this assembly is substantiated by its good electrical conductivity (similar to 10(-2) S cm(-1)). The on-surface assembly via both internally formed and externally added sheaf-like seeds open new pathways in supramolecular chemistry and device applications.

Synthesis of orthorhombic-molybdenum trioxide (α-MoO3) thin films by hot wire-CVD and investigations of its humidity sensing properties - Jadkar, Vijaya; Pawbake, Amit S.; Waykar,Ravindra G.; Jadhavar, Ashok Arjun; Mayabadi, Azam; Date, Abhijit; Late, Dattatray J.; Pathan, Habib M.; Gosavi, Suresh W.; Jadkar, Sandesh R. (Journal of Materials Science Materials in Electronics, 2017)
In present work, we report synthesis of orthorhombic-molybdenum trioxide (α-MoO 3) thin films using home-build hot wire-CVD (HW-CVD) method simply by heating the Mo filament in a controlled O 2 atmosphere. The formation of α-MoO 3 was confirmed by low angle-XRD and Raman spectroscopy. Low angle-XRD analysis revealed that α-MoO 3 crystallites have orientations along (110), (101) and (111) directions while Raman spectroscopy analysis shows two prominent vibrational modes ~819 and ~994 cm −1 associated with Mo 2–O and Mo=O respectively. SEM and TEM analysis show the formation of nano-sheets like morphology of α-MoO 3 thin films. The SAED pattern shows highly crystalline nature of α-MoO 3. The humidity-sensing properties were investigated at room temperature by fabricating the two probe device. The humidity sensing results showed n-type behavior of α-MoO 3. The maximum humidity sensitivity of ~6957% along with response time of ~66 s and recovery time of ~5 s were observed for α-MoO 3 thin film humidity sensor device. Our results have opened up a new avenue to grow α-MoO 3 for humidity sensor applications.

Facilitated lithium storage in hierarchical microsphere of Cu2S-MoS2 ultrathin nanosheets - Kadam, Sunil R.; Kalubarme, Ramchandra S.; Deshmukh, Shrutika P.; Panmand, Rajendra P.; Kawade, Ujjwala, V.; Kulkarni, Milind, V.; Deo, Shriniwas S.; Gosavi, Suresh W.; Kale, Bharat B. (ChemistrySelect, 2018)
Considering the high energy density Lithium ion batteries have become one of the best option for next-generation energystorage technologies. Transition metal chalcogenide nanomaterials are promising electrodes for Lithium-ion batteries. Molybdenum based layered chalcogenide materials wisely studied for rechargeable Li-ion batteries, due to its two-dimensional (2D) layered structure and better specific capacity. The three-dimensional (3D) synthesis of microsphere by ultrathin nanosheets is necessary for practical applications. Herein, the fabrication of a unique hierarchical 2D layered Cu2S-MoS2 nanostructure was (ultrathin nanosheets) demonstrated via in situ assembling of two-dimensional (2D) growths in facile solvothermal technique. The structural study reveals the existence of Cubic Cu2S and Rhombohedral MoS2 phase. Morphological study by FESEM and TEM shows unique ultrathin nanosheets of similar to 10 nm thickness self-assembled in the form of layered microsphere. In Li- ion storage testing, Cu2S-MoS2 electrode exhibited good specific discharge capacity of 651 mAhg(-1) at 50 mAg(-1) applied current and maintained 320 mAhg(-1) after 100 cycles. The facilitated advanced electrochemical performance attributed to layered ultrathin Cu2S-MoS2 composite nanosheets.

Architecture of NaFe(MoO4)2 as a novel anode material for rechargeable lithium and sodium ion batteries - Tamboli, Asiya M.; Tamboli, Mohaseen S.; Praveen, C. S.; Dwivedi, Pravin Kumari; Karbhal, Indrapal; Gosavi, Suresh W.; Shelke, V, Manjusha; Kale, Bharat B. (Applied Surface Science, 2021)
In recent decades, particular focus has been given to enhance the capacity of LIBs and SIBs either by developing new materials or by modifying existing materials. Hence, we have demonstrated a new anode material i.e. sodium iron molybdate [NaFe(MoO4)2] for both LIBs and SIBs. NaFe(MoO4)2 has been successfully synthesized by solid-state combustion technique and tested as a promising new anode material for both LIBs and SIBs. A detailed analysis of the crystal structure has been performed using DFT calculations. NaFe(MoO4)2 crystallizes in the monoclinic phase with the space group C2/c (#15). FESEM also shows highly crystalline monoclinic shaped crystals of micron size. When evaluated as an anode material for LIBs, NaFe(MoO4)2 electrode exhibited electrochemical capacity of 920 mAhg- 1 in the second cycle at the current density of 50 mAg-1. Though capacity decreases on further cycling, the coulombic efficiency was maintained at 99% for 50 cycles. Significantly, a high discharge capacity of 100 mAhg- 1 was maintained at a very high rate of 1 Ag-1. On the other hand, we have also tested NaFe(MoO4)2 for SIBs which shows excellent reversible specific capacity i.e. 100 mAhg- 1 at the current density of 100 mAg-1 even after 500 cycles. This novel system has shown good stability for LIBs and SIBs which is hitherto unattempted.
Keywords: Electrochemical study; lithium-ion battery; Morphology; NaFe(MoO4)2; Sodium-ion battery

Microbial production of N-acetyl-D-glucosamine (GlcNAc) for versatile applications: biotechnological strategies for green process development - Das, Sancharini; Chowdhury, Chiranjit; Kumar, S. Pavan; Roy, Debasis; Gosavi, Suresh W.; Sen, Ramkrishna (Carbohydrate Research, 2024)
N-acetyl-D-glucosamine (GlcNAc) is a commercially important amino sugar for its wide range of applications in pharmaceutical, food, cosmetics and biofuel industries. In nature, GlcNAc is polymerised into chitin biopolymer, which is one of the major constituents of fungal cell wall and outer shells of crustaceans. Sea food processing industries generate a large volume of chitin as biopolymeric waste. Because of its high abundance, chitinaceous shellfish wastes have been exploited as one of the major precursor substrates of GlcNAc production, both in chemical and enzymatic means. Nevertheless, the current process of GlcNAc extraction from shellfish wastes generates poor turnover and attracts environmental hazards. Moreover, GlcNAc isolated from shellfish could not be prescribed to certain groups of people because of the allergic nature of shell components. Therefore, an alternative route of GlcNAc production is advocated. With the advancement of metabolic construction and synthetic biology, microbial synthesis of GlcNAc is gaining much attention nowadays. Several new and cuttingedge technologies like substrate co-utilization strategy, promoter engineering, and CRISPR interference system were proposed in this fascinating area. The study would put forward the potential application of microbial engineering in the production of important pharmaceuticals. Very recently, autotrophic fermentation of GlcNAc synthesis has been proposed. The metabolic engineering approaches would offer great promise to mitigate the issues of low yield and high production cost, which are major challenges in microbial bio-processes industries. Further process optimization, optimising metabolic flux, and efficient recovery of GlcNAc from culture broth, should be investigated in order to achieve a high product titer. The current study presents a comprehensive review on microbe-based eco-friendly green methods that would pave the way towards the development of future research directions in this field for the designing of a cost-effective fermentation process on an industrial setup.
Keywords: Genetic engineering; GlcNAc applications; Market status; Microbial bioprocess; N-acetyl-D-glucosamine; synthetic biology